ANTIOXIDANT POTENTIAL OF INDIAN GOOSEBERRY (Emblica officinalis) AQUEOUS EXTRACT IN CHICKEN MEAT BALLS - R. Abinayaselvi; D. Santhi; A. Kalaikannan; A. Natarajan; K. Rajendran (Indian Journal of Veterinary and Animal Sciences Research, 2025)
This study was conducted to evaluate the antioxidant potential of Indian gooseberry (Emblica officinalis) aqueous extract in chicken meat balls and the assessment of the physico-chemical and sensory properties of the meat balls. Chicken meat balls were prepared with the inclusion of Indian gooseberry aqueous extract (GBAE) at 0, 9%, 12% and 15% levels. The emulsion pH, product pH, emulsion stability and product yield were determined. DPPH scavenging activity (%) was studied to establish the antioxidant potential of the GBAE in the product. Sensory properties were evaluated using 8 point hedonic scale. Emulsion pH and product pH decreased  significantly (P